Pengenalan Bahasa Inggris Pada Kelas Permulaan Melalui Metode TPR (Total Physical Response) - Ririn Pusparini, ; Ulhaq Zuhdi, (Pendidikan Sekolah Dasar, 2010)
This article aims to describe how the TPR method can introduce English to the beginners or the first year of elementary school. In introducing English to very young learners (5-7 years old), students are not focused on reading and writing skills because students in this level are still in the level of introducing the letter, reading, and writing their first language (Indonesia language). On the other words, students concentrate on listening and speaking skills in learning English. The techniques used for students at 5-7 years old and related to TPR method are game, singing English songs,and telling story. Media used are picture, cards, realia, English song cassete,etc in hope that students can memorize English words easily.